The Implementation of Hand and Foot Massage Therapy for Hemodynamic Stability in Patients with Hemorrhagic Stroke: Case Study - Sumardi, Sulistia Nur; Must, Akhmad (Indonesian Contemporary Nursing Journal (ICON Journal), 2025)
Introduction: Stroke is a neurological disease with approximately 13.7 million new cases annually. The hemodynamics of patients may be affected by stroke. Hand and foot massage therapy is required to complement the treatment and prevent hemodynamic instability. Aims: This study aimed to investigate the implementation of hand and foot massage therapy to lower blood pressure and improve MAP, breath rate, and oxygen saturation.  Methods: Two patients with hemorrhagic stroke were recruited through purposive sampling for this case study, following a nursing care approach. The inclusion criteria were as follows: hemorrhagic stroke, partially controlled ventilator, MAP >70 mmHg, heart rate > 60 beats/min, respiration rate > 12 breaths/min, oxygen saturation ≤100%, age between 55 and 64 years, no fracture, and did not get no sedation or muscle relaxants. The therapy was implemented for 40 minutes in three days, with a hemodynamic check-up every 30 min before and after the therapy (pre- and post-treatment).  Results: The findings showed that Hand and foot massage therapy considerably affected the hemodynamics. Patients' vital sign rates showed a reduction in blood pressure to 13.3 and 8.3 mmHg, MAP decreased to 13 and 2.3 mmHg, heart rate decreased to 14 and 21 beats/min, respiration rate decreased to 2 and 1 breath per minute; meanwhile, oxygen saturation improved to 1 and 0.3%, respectively.  Conclusions: Patients' hemodynamics could be stabilized within three days by hand and foot massage therapy for 40 min. To get the optimum results, the therapy could be given regularly